Rancang Bangun Sistem Informasi Penjualan dan Stok Opname Berbasis Web pada CV Devindo Multi Wahana - Afif Nurfadhil Nugraha; Farizi Ilham; Rifky Bayu Saputra; Achmad Rafqi Ikhrom (CV. Shofanah Media Berkah, 2026)
CV Devindo Multi Wahana, a plastic product distribution company serving wholesalers, MSMEs, and retail buyers, currently faces operational challenges due to its reliance on manual paper-based bookkeeping, which leads to transaction recording errors, difficulty in real-time stock monitoring, delayed reporting, and data discrepancies during periodic stocktaking. This research aims to design and develop an integrated web-based sales and stocktaking information system using the Extreme Programming (XP) method through four essential stages: planning, design, coding, and testing. The system incorporates extensive features including barcode-based item management, Point of Sale (POS) transactions, supplier purchase management, real-time stock tracking, a stocktaking module, minimum stock notifications, and automated sales and purchase reports. The result of this study is a web-based application operating on a localhost environment that automates recording processes and minimizes inventory management errors, which is expected to enhance operational efficiency and enable CV Devindo Multi Wahana to monitor its sales and inventory in a more accurate and structured manner.